Risk Factors for Gastrointestinal Leak after Perforated Peptic Ulcer Disease Operative Repair. Issue 12 (December 2021) - Lund, Sarah; Chauhan, Kiran Kaur; Zietlow, John; Stephens, Daniel; Zietlow, Scott; Strajina, Veljko; Turay, David; Zielinski, Martin
Background: There are limited studies regarding the impact of post-operative leak on perforated peptic ulcer disease (PPUD) and conflicting results regarding routine drain placement in operative repair of PPUD. This study aims to identify risk factors for gastrointestinal leak after operative repair of PPUD to better guide intra-operative decisions about drain placement. Methods: We performed a retrospective cohort study at a tertiary care center from 2008 to 2019, identifying 175 patients who underwent operative repair of PPUD. Results: Patients who developed a leak (17%) were compared to patients who did not. Both hypoalbuminemia (albumin < 3.5 g/dL) ( P = .03) and duodenal ulcers ( P < .01) were identified as significant risk factors for leak. No significant difference was found between leak and no leak groups for AAST disease severity grade, repair technique, or pre-operative use of tobacco, alcohol, or steroids. Post-operative leaks were associated with prolonged hospital stay (29 days compared to 10, P < .01), increased complication rates (77% compared to 48%, P < .01), and increased re-operation rates (73% compared to 26%, <0.01). No difference was identified in patient characteristics or operative leak rates between patients who had drains placed at the index operation and those that did not. Discussion: Leak after operative PPUD repair is associated with significant post-operative morbidity. Hypoalbuminemia and duodenal perforations are significant risk factors for post-operative leaks.